Some Notes on Historical, Theoretical, and Empirical Background of DSGE Models - Martin Slanicay (Review of Economic Perspectives, 2014)
In this paper I present the historical, theoretical and empirical background of DSGE models. I show that the fundament of these models lies in optimizing agents framework and argue which impulses fueled the development of DSGE models. I demonstrate the evolution of DSGE models with an accent on the role and effects of the monetary policy, using distinction between RBC models and New Keynesian models. I explain the paradigm shift from the RBC models to the New Keynesian models by pointing out the main pitfalls of the RBC models and showing how adding nominal rigidities to the otherwise standard RBC models enhances empirical properties of these models. I also discuss how nominal rigidities are modeled in New Keynesian DSGE models and what the pros and cons of different approaches are. Finally, I review the most important New Keynesian theories of nominal rigidities and some of the empirical evidence on price and wage rigidities
Keywords: 330